A Study on the Relationship between Servant Leadership, Organizational Culture, and Job Satisfaction in Fitness Clubs - Kyongmin Lee; Yongseek Kim; Woojeong Cho (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
In the fi eld of organizational behavior theory, the infl uence of servant leadership and organizational culture on the job satisfaction of organization members has been actively studied to eff ectively achieve the goals set by the organization. However, there is a severe lack of studies on the relationship between servant leadership, organizational culture, and job satisfaction in the sport industry. Therefore, this study empirically analyzed the causal relationships among the three variables by surveying 320 employees in fi tness clubs located in Pusan, Korea. Surveys were conducted using the convenience sampling method, and a total of 300 surveys were used in the analysis. Data analysis methods included descriptive statistics analysis, exploratory factor analysis, reliability analysis, correlation analysis, and multiple regression analysis using SPSS 19.0. Key results from this study were as follows. First, servant leadership in fi tness clubs had a positive infl uence on organizational culture. Second, servant leadership in fi tness clubs had a positive infl uence on the job satisfaction of their employees. Third, the organizational culture of fi tness clubs had a positive infl uence on the job satisfaction of employees. The results of this study can contribute to establishing strategies to advance the organizational performance and eff ective human resource management of fi tness clubs.